Allergy to Prolene Sutures in a Dural Graft for Chiari Decompression - Iahn Cajigas; S. Shelby Burks; Joanna Gernsback; Lauren Fine; Baharak Moshiree; Allan D. Levi (Case Reports in Medicine)
Allergy to Prolene suture is exceedingly rare with only 5 cases reported in the literature. There have been no such cases associated with neurosurgical procedures. Diagnosis is nearly always delayed in spite of persistent symptomatology. A 27-year-old girl with suspected Ehlers-Danlos, connective tissue disorder, underwent posterior fossa decompression for Chiari Type 1 malformation. One year later, the patient presented with urticarial rash from the neck to chest. Cerebrospinal fluid and blood testing, magnetic resonance imaging, and intraoperative exploration did not suggest allergic reaction. Eventually skin testing proved specific Prolene allergy. After suture material was removed, the patient no longer complained of pruritus or rash. This single case highlights the important entity of allergic reaction to suture material, namely, Prolene, which can present in a delayed basis. Symptomatology can be vague but has typical allergic characteristics. Multidisciplinary approach is helpful with confirmatory skin testing as a vital part of the workup.